Effect of the ZrO2–Al2O3 solid solution on the performance of Ni/ZrO2–Al2O3 catalysts for CO2 methanation. (10th November 2021) - Chang, Shuai; Na, Wei; Zhang, Jiaqi; Lin, Lina; Gao, Wengui
Abstract : The appropriate addition of Al2 O3 to form a ZrO2 -Al2 O3 solid solution will weaken the Ni-ZrO2 interaction and increase the concentration of basic sites and oxygen vacancies in the catalyst, resulting in better activation of CO2 . Abstract : The conversion of CO2 into value-added chemicals has attracted a lot of attention, not only reducing the concentration of CO2 in the air, but also generating chemicals and fuels, which are of great importance to solve the growing environmental and energy problems. Ni catalysts with different Zr/Al ratios were prepared by co-precipitation and impregnation for CO2 methanation. The activity test results showed that almost 100% CH4 selectivity and 82.6% CO2 conversion were obtained at a reaction temperature of 350 °C when the Zr/Al ratio was 1. The physicochemical properties of the catalysts were investigated using XRD, N2 adsorption–desorption, H2 -TPR, H2 -TPD, CO2 -TPD, XPS and TEM, and the surface-generating substances and methanation reaction mechanism of the catalysts were explored using in situ DRIFTS characterisation. The experimental results show that the addition of Al2 O3 to Ni/ZrO2 weakens the Ni–ZrO2 interaction and promotes the reduction and dispersion of NiO through the solid solution bonding of ZrO2 –Al2 O3 . The in situ DRIFTS results show that there are more formate adsorbed species on the surface of the Ni/ZrO2 –Al2 O3 catalyst compared to the Ni/ZrO2 catalyst, which is the main formation substance for CO2 methanation.